Optimalisasi Metode Muraja'ah Pada Program Tahfiz Qur'an di MTs Al-Washliyah 30 Pematang Guntung Kabupaten Serdang Bedagai - Luthfiah Nur Al-Banjari (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study was to describe the optimization of the Muraja'ah method in the Tahfiz Qur'an program at MTS Al Washliyah 30 Pematang Guntung, Serdang Bedagai Regency and to find out the constraints faced by MTS Al Washliyah 30 Pematang Guntung in optimizing the Muraja'ah method. This study was designed using a qualitative approach. The data collection techniques used was interview observation, observation, and documentation. While the data analysis technique includes 3 things, namely: Data analysis techniques, data interpretation in this study follow data condensation, data presentation, and conclusion drawing and verification. The results showed that the MTS Al Washliyah 30 Pematang Guntung school in the Tahfiz Qur'an Program had optimized the muraja'ah method on students well. The optimization of the muraja'ah method is carried out by teachers in various ways, namely first, depositing memorization both inside and outside the classroom. Second, re-read the memorization that has been memorized, and third, give memorization tasks at home.